Skärsläckaren : Ett beslutsunderlag - Bergström, Sofie (2011)
The cutting extinguisher is a tool that can be used both to penetrate different constructions and fighting fires. The equipment is meant to work as a complement to traditional smoke diving. The cutting extinguisher is supposed to have the power to extinguish fires in the early stage or lower the temperature in a room enough to make the work environment considerably better for the firemen. The rescue service in the municipality of Piteå is considering an investment in a cutting extinguisher for their fire station in Piteå. The purpose of the report is to provide a basis for a decision on a possible purchase of a cutting extinguisher to the rescue service in Piteå. Issues about function, costs and how the cutting extinguisher is used will be discussed. Information about the cutting extinguisher has been collected from literature and the manufacturer. Incident reports from the rescue service have been studied to be able to find out if the cutting extinguisher may be of use in the municipality of Piteå. Incident reports (regarding fire in buildings) from year 2003 to 2007 have been the basis for estimating how many times a year the cutting extinguisher may be of use. Furthermore a survey has been done, where a number of rescue services in Sweden (that have one or more cutting extinguishers) have answered questions about their current use of the equipment. Based on the incident reports and the author’s own analysis of these the cutting extinguisher may have been of use at 14 incidents of fire in buildings during the years 2003-2007. This results in about three incidents a year. This number could be a little higher if all incident reports had been studied, since the cutting extinguisher also can be used at other types of fires and at penetration of constructions. The total cost for the cutting extinguisher, educating two employees and the yearly maintenance during the first year will be 382 000 Swedish crowns. Note that costs for mounting and value-added tax are not included, neither are the costs for accommodation ...